Pemblokiran Lahan oleh Developer Perumahan secara Melawan Hukum Sesuai Putusan Pengadilan Nomor 43/Pdt.G/2022/PN.Tjk - Anggalana, Anggalana; Ainita, Okta; Rinaldy, Dion (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
Communities that own or control land often experience disputes. Community understanding of land ownership is still relatively minimal knowledge about it. The purpose of this article is to find out the forms of unlawful acts of blocking other people’s land on other people’s land based on Civil Law and other legislation in accordance with decision Number 43/Pdt.G/2022/PN.Tjk. The research method in this writing uses a normative legal approach based on positive law, and based on literature. Expropriation activity implies taking rights or assets arbitrarily or ignoring statutory regulations. Some concrete forms of land grabbing include stealing, seizing, seizing, or physically seizing other people's legitimate land or houses, demanding ownership rights secretly, carrying out illegal stakes or fencing, cultivating land, selling land rights, and displacing or forcibly evicting the actual landowners. Based on civil law, people who commit land grabs can be charged with unlawful acts. It can be seen that in cases of land grabbing there are parties who sue and demand compensation for the losses suffered. In addition, land grabbing is also an act of someone entering the land without rights. ___ Referensi Buku dengan penulis: Abdurrahman. (1991). Masalah Hak-hak Atas Tanah dan Pembebasan Tanah di Indonesia. Bandung: Citra Aditya Bakti. Adistie, N., dan Anwar, J. (2021). Hubungan Keabsahan Pengalihan Piutang (Cessie) yang Dilakukan secara Berulang Kali terhadap Perpindahan Hak Tanggungan Milik Debitur. Yustisia Tirtayasa: Jurnal Tugas Akhir, 1(1), 93-117. Asshiddiqie, Jimmly. (2005). Konstitusi dan Konstitusionalisme Indonesia. Jakarta: Konstiusi Press Diantha, I. M. P. (2016). Metodologi Penelitian Hukum Normatif dalam Justifikasi Teori Hukum. Jakarta: Prenada Media. Gautama, Sudargo. (1990). Tafsiran Undang-Undang Pokok Agrarian. Bandung: Citra Aditya Bakti. Harsono, Boedi. (2007). Hukum Agraria Indonesia, Peraturan-Peraturan Hukum Tanah. Klaten: Intan Sejati. Supriadi. (2008). Hukum Agraria. Jakarta: Sinar Grafika. Yosua, Suhanan. (2018). Hak Atas Tanah Timbul (Aanslibbing) Dalam Sistem Hukum Pertanahan Indonesia. Jakarta: Restu Agung. Artikel jurnal: Chayadi, L. (2020). Implikasi Hukum Atas Kedudukan Warga Negara Asing sebagai Ahli Waris untuk Hak Milik Atas Tanah. Jurnal Ilmiah Penegakan Hukum, 7(2), 159-168. Hartono, B., dan Aprinisa, A. (2021). Implementasi Sanksi Pidana Pelaku Tindak Pidana Kejahatan terhadap Nyawa Orang Lain yang Direncanakan (Pembunuhan Berencana). Jurnal Penelitian & Pengkajian Ilmiah Mahasiswa (JPPIM), 2(4), 31-44. Istiqamah, I. (2018). Tinjauan Hukum Legalisasi Aset melalui Pendaftaran Tanah Sistematis Lengkap (PTSL) terhadap Kepemilikan Tanah. Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 5(1), 226-235. Mahanani, A. E. E. (2021). Pemetaan Normatif Logika Pengecualian Keputusan Tata Usaha Negara Dalam Penyelesaian Sengketa Tata Usaha Negara. Widya Pranata Hukum: Jurnal Kajian dan Penelitian Hukum, 3(1), 76-89. Oktoyoki, H., Ansiska, P., dan Ifebri, R. (2022). Peran Pemerintah Dalam Masalah Tenure dan Land Management untuk Pengembangan Hutan Rakyat. Geoforum, 1(2), 18-26. Pahlevi, R. R., Zaini, Z. D., dan Hapsari, R. A. (2021). Analisis Perbuatan Melawan Hukum (Onrechtmatigedaad) terhadap Sengketa Kepemilikan Hak Atas Tanah. Pagaruyuang Law Journal, 5(1), 18-28. Ramadhani, R. (2017). Jaminan Kepastian Hukum yang Terkandung Dalam Sertipikat Hak Atas Tanah. De Lega Lata: Jurnal Ilmu Hukum, 2(1), 139-157. Ramadhani, R. (2021). Pendaftaran Tanah sebagai Langkah Untuk Mendapatkan Kepastian Hukum terhadap Hak Atas Tanah. Sosek: Jurnal Sosial dan Ekonomi, 2(1), 31-40. Sari, I. (2020). Hak-hak Atas Tanah Dalam Sistem Hukum Pertanahan di Indonesia menurut Undang-Undang Pokok Agraria (UUPA). Jurnal Mitra Manajemen, 9(1), 15-33. Susanto, B. (2014). Kepastian Hukum Sertifikat Hak Atas Tanah Berdasarkan Peraturan Pemerintah Nomor 24 Tahun 1997. DiH: Jurnal Ilmu Hukum, 10(20), 76-82.